Ear Infection and Its Associated Risk Factors in First Nations and Rural School-Aged Canadian Children - Chandima P. Karunanayake; William Albritton; Donna C. Rennie; Joshua A. Lawson; Laura McCallum; P. Jenny Gardipy; Jeremy Seeseequasis; Arnold Naytowhow; Louise Hagel; Kathleen McMullin; Vivian Ramsden; Sylvia Abonyi; et al. (Hindawi Limited, 2016)
Background. Ear infections in children are a major health problem and may be associated with hearing impairment and delayed language development. Objective. To determine the prevalence and the associated risk factors of ear infections in children 6-17 years old residing on two reserves and rural areas in the province of Saskatchewan. Methodology. Data were provided from two rural cross-sectional children studies. Outcome variable of interest was presence/absence of an ear infection. Logistic regression analysis was conducted to examine the relationship between ear infection and the other covariates. Results. The prevalence of ear infection was 57.8% for rural Caucasian children and 43.6% for First Nations children living on-reserve. First Nations children had a lower risk of ear infection. Ear infection prevalence was positively associated with younger age; first born in the family; self-reported physician-diagnosed tonsillitis; self-reported physician-diagnosed asthma; and any respiratory related allergy. Protective effect of breastfeeding longer than three months was observed on the prevalence of ear infection. Conclusions. While ear infection is a prevalent condition of childhood, First Nations children were less likely to have a history of ear infections when compared to their rural Caucasian counterparts.